Cecil the lion in the British media: The pride and prejudice of the press. (1st September 2017) - Somerville, Keith
When US talk show host Jimmy Kimmel shed tears on his TV show about the killing of a lion that had been nicknamed Cecil, he helped unleash a storm of media coverage, social media response and comment that shed an interesting light on media coverage of wildlife and conservation issues. The killing of the lion in Zimbabwe in July 2015 led to media coverage of an unprecedented nature. The media hits on the story were greater than for any previous conservation story in living memory. But the tone and content of the stories was also as important as the scale. The use of language was hyperbolic, the attention to detail poor and the use of sources fell outside what is normally considered good journalistic practice. This article analyses the coverage of the story in the British media and the likely effects for the understanding of lion conservation and wildlife in general.